Western rubber planting enterprise in Southeast Asia, 1876-1921 - Voon, Phin Keong (Penerbit Universiti Malaya, 1976)
1. Diffusion of Rubber in South and Southeast Asia ; 2. The Period of Exper imentation; Pioneer plantings,...